Integrated miRNA-mRNA analysis reveals the molecular mechanism in mandarin fish (Siniperca chuatsi) in response to fresh baits and artificial diets feeding - Hongyan Li; Shuhui Niu; Houjun Pan; Guangjun Wang; Jun Xie; Jingjing Tian; Kai Zhang; Yun Xia; Zhifei Li; Ermeng Yu; Wangbao Gong (Aquaculture Reports, 2023)
The complete replacement of fresh baits (FB) by formulated artificial feeds (AF) after domestication in mandarin fish (Siniperca chuatsi) has matured in recent years, while the underlying molecular events of long-term AF diet feeding after diet shifts remained unclear. Therefore, mandarin fish, which had been successfully domesticated, were fed with the FB or AF for 180 days to explore the molecular mechanisms underlying the differences due to shifted food habit. Compared to the FB group, slight intestinal histological damage was found in the AF group of mandarin fish. An integrated analysis of miRNA-mRNA sequencing and their interaction networks was conducted between the FB and AF groups. The result showed that a total of 209 differentially expressed mRNAs (DEmRNAs) and 2 differentially expressed miRNAs (DEmiRNAs) with significance were identified. The DEmRNAs were enriched to 39 pathways including tight junction, steroid biosynthesis and protein processing in ER. Oni-Let-7a and aca-Let-7i were the two significantly identified DEmiRNAs, whose target prediction was enriched with GO terms and KEGG pathways including TGFβ signaling pathway, steroid biosynthesis, and retinol metabolism. In general, our research was the first exploration to characterize the interacted miRNA-mRNA sequencing of mandarin fish fed the FB and AF diets, which could reveal the mechanisms of long-term adaptation to new foods in organisms who subjected to a food conversion in their early life. Data Availability Statement: The dataset generated by deep-sequencing platforms was deposited in the NCBI Sequence Read Archive (SRA, http://www.ncbi.nlm.nih.gov/Traces/sra). The NCBI Sequence Read Archive accession number is PRJNA897748.